Introduction of Modified BglBrick System in Lactococcus lactis for Straightforward Assembly of Multiple Gene Cassettes - Plavec, Tina Vida; Ključevšek, Tim; Berlec, Aleš (Frontiers in Bioengineering and Biotechnology, 2021)
Genetic modification of lactic acid bacteria is an evolving and highly relevant field of research that allows the engineered bacteria to be equipped with the desired functions through the controlled expression of the recombinant protein. Novel genetic engineering techniques offer the advantage of being faster, easier and more efficient in incorporating modifications to the original bacterial strain. Here, we have developed a modified BglBrick system, originally introduced in Escherichia coli and optimized it for the lactic acid bacterium Lactococcus lactis. Six different expression cassettes, encoding model proteins, were assembled in different order as parts of a modified BglBrick system in a novel plasmid pNBBX. All cassettes included nisin promoter, protein encoding gene and transcription terminator. We demonstrated successful intracellular expression of the two fluorescent proteins and display of the four protein binders on the bacterial surface. These were expressed either alone or concomitantly, in combinations of three model proteins. Thus, a modified BglBrick system developed herein enables simple and modular construction of multigene plasmids and controlled simultaneous expression of three proteins in L. lactis.